The Effectiveness of Computer Assisted Instruction (CAI) Supported by GeoGebra in Enhancing Students’ Mathematical Representation Ability - Rahmatudin, Jajang; Serlina, Serlina (Papanda Publisher, 2024)
This study aims to determine the effectiveness of the Computer Assisted Instruction (CAI) learning model supported by GeoGebra in improving students' mathematical representation ability. The research was conducted at SMP Negeri 2 Kuningan with two eighth-grade classes as the sample. The experimental class received instruction using the CAI model with GeoGebra, while the control class was taught using a conventional model. The research design employed a quasi-experimental method with a non-equivalent pretest-posttest control group. Prior to the intervention, a validation test was conducted on eight essay items through four analyses: validity, reliability, item difficulty, and discrimination index. Data collection involved pretests, six instructional sessions, posttests, and a student response questionnaire. The Mann–Whitney U test was used for hypothesis testing. The results indicated no significant difference in pretest scores between the groups. However, posttest results and N-Gain analysis showed significant improvement in the experimental class. The average response percentage was 83%, categorized as very positive. These findings suggest that the CAI model supported by GeoGebra is effective in enhancing students’ symbolic, visual, and verbal mathematical representation skills, as well as fostering positive student attitudes toward mathematics learning.